2022
DOI: 10.1038/s41467-022-32714-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically stable and amplified circularly polarized excimer emission regulated by solvation of chiral co-assembly process

Abstract: Chiral supramolecular assembly has been assigned to be one of the most favorable strategies for the development of excellent circularly polarized luminescent (CPL)-active materials. Herein, we report our study of an achiral boron-containing pyrene (Py)-based chromophore (PyBO) as a circularly polarized excimer emission (CPEE) dye induced by chiral co-assemblies containing chiral binaphthyl-based enantiomers (R/S-M). Chiral co-assembly R/S-M-(PyBO)4 fresh film spin-coated from toluene solution can exhibit order… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 48 publications
1
20
0
1
Order By: Relevance
“…Very recently, we also reported three kind of chiral co‐assemblies spin‐costed from toluene (Path A), DCM (Path B) and THF (Path C) solutions, by choosing achiral boron‐containing Py‐based chromophore (PyBO) as a circularly polarized excimer emission (CPEE) dye and R ‐/ S ‐M as chiral inducers, which named R ‐M‐(PyBO) 4 , R ‐M‐(PyBO) 4 ‐D and R ‐M‐(PyBO) 4 ‐T, respectively (Figure 5c). [24c] As expected, all fresh films showed good CPEE behaviors from PyBO excimer (λ em =515 nm, g em =+0.45, +0.42 and +0.62, respectively), which was ascribed to asymmetrically steric architectures in the excited states and the formation of chiral co‐assemblies driven by intermolecular π–π stacking interactions. However, as spherulite growth, the CPEE signals of R ‐M‐(PyBO) 4 and R ‐M‐(PyBO) 4 ‐D gradually disappeared and converted into very weak CPL signals from PyBO monomer emission (λ em =461 nm, g em =+0.0125 and +0.009) (Figure 5d and 5e).…”
Section: Induced Cpl Materials Based On Chiral Supramolecular Co‐asse...supporting
confidence: 69%
“…Very recently, we also reported three kind of chiral co‐assemblies spin‐costed from toluene (Path A), DCM (Path B) and THF (Path C) solutions, by choosing achiral boron‐containing Py‐based chromophore (PyBO) as a circularly polarized excimer emission (CPEE) dye and R ‐/ S ‐M as chiral inducers, which named R ‐M‐(PyBO) 4 , R ‐M‐(PyBO) 4 ‐D and R ‐M‐(PyBO) 4 ‐T, respectively (Figure 5c). [24c] As expected, all fresh films showed good CPEE behaviors from PyBO excimer (λ em =515 nm, g em =+0.45, +0.42 and +0.62, respectively), which was ascribed to asymmetrically steric architectures in the excited states and the formation of chiral co‐assemblies driven by intermolecular π–π stacking interactions. However, as spherulite growth, the CPEE signals of R ‐M‐(PyBO) 4 and R ‐M‐(PyBO) 4 ‐D gradually disappeared and converted into very weak CPL signals from PyBO monomer emission (λ em =461 nm, g em =+0.0125 and +0.009) (Figure 5d and 5e).…”
Section: Induced Cpl Materials Based On Chiral Supramolecular Co‐asse...supporting
confidence: 69%
“…Conjugated π-electron systems of nanostructured aromatic macrocycles are of peculiar interests in synthetic organic chemistry because they exceptionally show the unique cyclic π conjugation with either a parallel or radial orientation of p z orbitals. Various topologically remarkable structures have been afforded by their contorted π-systems which, in turn, induced enduring attractions in optoelectronic materials and supramolecular assemblies. Merging the concept of molecular chirality with π-conjugated macrocyclic chemistry has recently been revitalized for emergent applications in chiral sensing, enantioselective encapsulation, three-dimensional (3D) displays, and chiroptical materials. Despite this much attention, access to the structurally strained and rigid chiral frameworks has long been considerably challenging. Previous studies revealed that the open-chain analogues were extensively explored as the chirality could be achieved on molecular level or in the aggregated phases of assembled superstructures . In sharp contrast, only a small number of carbon-based π-conjugated chiral macrocycles have been established via several approaches: (I) Inherent chirality derived from the orientation-constrained cyclic motifs without any symmetry other than the C 1 axis; such group of planar chirality has been proposed by Isobe in the synthesis of cyclochrysenylenes and also demonstrated by Du’s work on cycloanthracenes; (II) symmetry breaking of initially achiral macrocycles via partial replacement of the cyclic backbones with a secondary building block; (III) topologically defined macrocycles that are represented by the well-known figure-eight biscyclic and pioneered in several groups; and (IV) stereogenic element embedded cycles with highly controllable chiral functionality (Scheme a). ,− Very recently, impressive advances have come to our attention in quest of the fully fused chiral nanobelts, as reported by Miao, Tanaka, Isobe and Wu, and Ito and Itami…”
Section: Introductionmentioning
confidence: 99%
“…Chiral binaphthyl derivatives have garnered tremendous attention for their modifiable molecular structures. [198][199][200] For example, Akagi and coworkers employed cationic poly(paraphenylene) to form CPL-active polymer spherulites with anionic chiral binaphthyl. [201] The results implied that the polymer assemblies had induced chirality imparted by axially chiral compound.…”
Section: Chiral Component and Luminescent Component: Non-covalent Int...mentioning
confidence: 99%